Accounting information systems in Aceh: a study on critical success factors of disaster recovery plan adoption - Yusmita, Fifi (2020)
The impact of disasters can have a very widespread negative effect. In the context of the Accounting Information System (AIS), disasters significantly destroy its function, interrupt organizational functions, and also cripple the organization’s activities. Therefore, given that disasters have been occurring more frequently lately, it is crucial for organizations to protect their AIS from the negative consequences of disasters by having a Disaster Recovery Plan (DRP) in place. DRP can offer a proper recovery strategy to salvage, keep, and run AIS functions after chaotic situations, such as natural disasters. DRP for AIS is therefore essential for any organization that wants to protect its data and information. This study was developed to determine the Critical Success Factors (CSFs) that influence the DRP adoption for the AIS and to study the perception of stakeholders in local government organizations towards the adoption of DRP for AIS. A mixed-method approach, which uses both quantitative and qualitative research methods, was employed to validate and test the conceptual model. The method was also used to understand the adoption of DRP for AIS. Questionnaires and semi-structured interviews were the two methods of data collection in this study. Through these two data collection methods, a total of 209 questionnaires from government employees were analyzed to generate solid descriptions and interpretations of factors influencing DRP adoption for AIS among the local government organizations. This study has identified 97 CSFs for DRP adoption of AIS. Based on the quantitative analyses, this study provides the conceptual model of the adoption of DRP for AIS. This model introduces several CSFs that influence the adoption of DRP for AIS amongst local government organizations in the province of Aceh. Furthermore, based on the qualitative analyses, it was found that top management commitment, human resources, and budgeting as the CSFs, while human resources and human skills, changes in regulations and politics, the commitment of top management, and budgeting were found as the barriers to adopting the DRP for AIS. The research findings of this study can assist local government organizations, researchers, and policymakers to understand the importance of DRP adoption for AIS in dealing with unpredictable disasters with various barriers to implement it.